Investigating English Writing Errors Among Senior High School Students in North Bali: An Error Analysis of English as a Foreign Language (EFL) Learners - Suputra, I Gede Widya (Indo-MathEdu Intellectuals Journal, 2026)
Writing in English remains one of the most challenging skills for English as a Foreign Language (EFL) learners, particularly in achieving grammatical accuracy. Although previous research has extensively classified grammatical errors, qualitative studies on the factors underlying these errors in high school students in North Bali are still limited. This study aims to identify the types of English writing errors and analyze the factors contributing to their occurrence. The study employed a qualitative case study design with data obtained through student writing assignments, semi-structured interviews, and learning support documents. Data were analyzed using the principles of Error Analysis and thematic analysis. The results identified five main categories of errors: omission, misinformation, misordering, overgeneralization, and global errors, with omission being the most dominant category. Interview analysis indicated that these errors were influenced by first language interference, limited grammatical knowledge, literal translation, limited exposure to English, and classroom learning experiences. These findings suggest that writing errors are the result of an interaction of linguistic, cognitive, and instructional factors. Pedagogically, the research findings emphasize the importance of contextual grammar instruction, meaningful writing practice, and constructive corrective feedback in EFL learning.